The impediments to marriage arising from the ethical and legal node - STAWNIAK, HENRYK (Prawo Kanoniczne, 2012)
The article presents the impediment of consanguinity, affinity, public propriety and the legal relationship as those impediment from ethical and legal node. These are presented the rationale for the existence of these impediments and their origins, it also brings a range of impediments and legislative trends in this regard. There will be also presented the questionable and controversial issues in the interpretation of the mentioned impediments to the marriage. The impediments themselves, according to a study, were used as the defense of the dignity of the family, creating the appropriate intra-family relationships, creating and deepening the bonds of friendship and love between people, and also served, for reasons of eugenics, the protection of the individuals’ health and society.